Submission of Copy of Determination Order Regarding The Provisional Discontinuation of Civil Servants - Isfandika Isfandika; Mohd. Din; Iman Jauhari (Syiah Kuala Law Journal, 2021)
Law Number 5 of 2014 concerning State Civil Apparatus stipulates that Civil Servants (PNS) who are detained because they are designated as criminal suspects are temporarily dismissed as PNS, but Law Number 8 of 1981 concerning the Criminal Procedure Code (KUHAP) only requires that a copy of the warrant for further detention or detention or a judge's decision be given to the family of the suspect. This study aims to determine and explain the impact of the absence of provisions in the Criminal Procedure Code regarding copies of detention orders to the Civil Service Supervisory Officer on the temporary dismissal of Civil Servants who are detained because they are designated as suspects. The approach method used in this research is normative juridical. The results of this study indicate that the absence of provisions in the Criminal Procedure Code regarding copies of detention warrants to Civil Service Supervisors related to Civil Servants who are detained because they are designated as suspects causes the issuance of Temporary Dismissal Decrees is often late.